Effect of Natural and Synthesized Oil Blends with Diesel by Volume on Lubrication and Performance of Internal Combustion Engine - Palikhel, Laxman; Karn, Rupesh Lal; Aryal, Suman; Neupane, Barsha (Journal of Innovations in Engineering Education, 2020)
Use of ultra-low sulfur diesel leads to improve emission but it has negative impact on lubrication. Poor lubrication leads to damage the cylinder parts and piston rings. For proper lubrication in ultra-low sulfur diesel, anti-wear agent, corrosion & Rust inhibitor, metal deactivator, Anti-oxidant, Pour point depressant, seal swell agent, viscosity improver and other are used. Viscosity improver such as polymers and copolymers of methacrylates, butadiene olefins and alkylated styrenes reduce the rate of viscosity change with temperature, metal deactivator are organic complexes containing nitrogen or sulphur, amines, sulphides and phosphites reduce catalytic effect on metals on oxidation rate, anti-wear agent such as Zinc dithiophosphates, organic phosphates and acid phosphates reduces friction and wear and prevent scoring and seizure. In this paper comparison of 5% blend of commercially available synthesized lubricating oil mixed with pure diesel by volume and 5% blend of transesterified Jatropha with pure diesel by volume is investigated. It is found that for the same brake power, indicated power provided by 5% blend of transesterified Jatropha is lower than 5% blend of lubricating oil. The friction loss for 5% blend of transesterified Jatropha is lower than 5% blend of lubricating oil. Throughout the load specific fuel consumption of 5% blend of transesterified Jatropha is lower than 5% blend of lubricating oil except at low load (i.e. before 1.5kg). Other performance parameters such as indicated thermal efficiency, brake thermal efficiency, volumetric efficiency and mechanical efficiency also support the fact that 5% blend of transesterified Jatropha shows a better performance characteristics than 5% blend of lubricating oil.